Comparison of alpha–theta neurofeedback versus sensorimotor rhythm neurofeedback in the treatment of patients with fibromyalgia: A randomized, double-blind, controlled clinical trial - Samaneh Farnia (Chronic Diseases Journal, 2020)
BACKGROUND: Fibromyalgia (FM) is a chronic disease with widespread musculoskeletal pain. In this study, we used neurofeedback to reduce pain and enhance the quality of life (QOL).